2011
DOI: 10.1128/iai.01139-10
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vaccination with a Multivalent, Live-Attenuated Vaccine Induces Multifactorial Immunity against Pseudomonas aeruginosa Acute Lung Infection

Abstract: Many animal studies investigating adaptive immune effectors important for protection against Pseudomonas aeruginosa have implicated opsonic antibody to the antigenically variable lipopolysaccharide (LPS) O antigens as a primary effector. However, active and passive vaccination of humans against these antigens has not shown clinical efficacy. We hypothesized that optimal immunity would require inducing multiple immune effectors targeting multiple bacterial antigens. Therefore, we evaluated a multivalent live-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 38 publications
0
42
0
2
Order By: Relevance
“…Therefore, the activation of the host immune response elicited by P. aeruginosa OMVs is dependent primarily on LPS via the TLR4 signaling pathway but requires an intact membrane struc- Our study provides further evidence that development of a pseudomonal vaccine based on OMVs of P. aeruginosa is a promising approach. Vaccines that effectively prevent P. aeruginosa pulmonary infections could be very useful, and previous studies suggested that LPS is an influential effector in the development of vaccines in mice (20)(21)(22)51). Ramphal et al also showed that Pseudomonas LPS is not a key virulence factor in acute pneumonia and thus can be used as an adjuvant to trigger a prominent proinflammatory response and effectively defend the lung from P. aeruginosa infection (52).…”
Section: Fig 4 Lysed P Aeruginosamentioning
confidence: 99%
“…Therefore, the activation of the host immune response elicited by P. aeruginosa OMVs is dependent primarily on LPS via the TLR4 signaling pathway but requires an intact membrane struc- Our study provides further evidence that development of a pseudomonal vaccine based on OMVs of P. aeruginosa is a promising approach. Vaccines that effectively prevent P. aeruginosa pulmonary infections could be very useful, and previous studies suggested that LPS is an influential effector in the development of vaccines in mice (20)(21)(22)51). Ramphal et al also showed that Pseudomonas LPS is not a key virulence factor in acute pneumonia and thus can be used as an adjuvant to trigger a prominent proinflammatory response and effectively defend the lung from P. aeruginosa infection (52).…”
Section: Fig 4 Lysed P Aeruginosamentioning
confidence: 99%
“…We have shown that the ⌬lpp ⌬msbB mutant was more attenuated than the single mutants (i.e., the ⌬lpp or ⌬msbB mutant) alone in a mouse model of pneumonic plague and that it generated cell-mediated immune responses (43). On the other hand, studies have also implicated opsonic antibodies to the antigenically variable LPS O antigens as primary immune effectors against Pseudomonas aeruginosa-associated acute lung infection (59,60). Therefore, fine-tuning of attenuation and the immunogenicity is a key to the development of a successful live-attenuated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Live vaccines typically generate optimal protection against infectious agents by stimulation of multiple immune effectors that target a broad spectrum of antigenic molecules of the pathogen (18). Immunization of C57BL/6 mice with a previously described live, attenuated "⌬T" vaccine strain of Coccidioides has been shown to induce protection against pulmonary coccidioidal infection based on early reduction of parasitic cell number and containment of the organism (43).…”
Section: Discussionmentioning
confidence: 99%